Supplemental Work at Home among Finnish Wage Earners: Involuntary Overtime or Taking the Advantage of Flexibility? - Ojala, Satu (Nordic Journal of Working Life Studies, 2011)
It is suggested, that the new flexible work practices are enhanced to meet the work-family demandsand therefore benefit especially women. In the article the focus is on informal flexibilitytaking place at home, for which field studies of the role of gender are rare. Against the assumptions,paid work at home is mostly informal, supplementary overtime by nature. In this article, I explorewhy employees undertake work in their private sphere during their free time and whether gendermakes a difference there. I carry out both qualitative and quantitative analyses. The qualitativedata consists of 21 interviews with white-collar employees and the quantitative data from theFinnish Quality of Work Life survey 2008 for which there are almost 4400 respondents. The methodsinclude content analysis, descriptive statistics and logistic regression analysis.According to both the qualitative and quantitative data, job characteristics play the most importantrole for all who work at home; employees with higher education, or supervisory tasks, inparallel with having an autonomous and inspiring job predict both tele- and supplemental work.Importantly, gender plays only a minor role in the puzzles of choosing when and where to work.The social relations at the workplace, including the atmosphere and the support of superiors andthe work community, are only weakly related to work at home. At the same time, supplementalwork is associated with great time pressure and involuntary overtime.